(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article analyzes the pedagogical and psychological aspects of the formation of the personality of modern students. Functional models, individualized teaching methods, and cluster-based educational strategies aimed at the formation of the personality of a modern student are considered. The study presents innovative approaches that stimulate academic, social, and emotional development, in line with Uzbek educational reforms and global trends. The article provides practical recommendations for improving the education system and creates a basis for future research.